QUATERNARY SPECIFIC CAPACITY ASSESSMENT OF NEW PERSPECTIVES OF EDUCATION (GYMNASIUM, 2009)
In the study of measurements aimed at assessing driving ability for new perspectives of educationexpressed through integrated education, inclusive education and interdisciplinary.So to work at this age are considered necessary to evaluate the main trends currently learning(integration, interdisciplinarity, etc..).Efficiency problem of the relationship between theory and educational practice in general and thediscipline of physical education in particular, is for us an ongoing subject of optimization by focusing equalattention to two aspects of teaching, information and format of transferring specific gravity of educatededucated.